IMMUNOLOGICAL CHANGES IN HIV-INFECTED CHILDREN WITH VIRAL DIARRHEA (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Diarrhea is a common condition among 30–60% of HIV-infected patients in developed countries, whereas in low- and middle-income countries, almost 90% of individuals with HIV suffer from diarrhea. Intestinal infections are the main cause of diarrhea in these populations [Wondmieneh A, Gedefaw G, Alemnew B. Intestinal parasitic infections and associated factors among people living with HIV/AIDS in Ethiopia. PLoS One. 2020].